An assessment of sensory sensitivity, including certain anhedonia dimensions, in patients with schizophrenia using transcutaneous electrical nerve stimulation - Joanna Witkoś; Agnieszka Fusińska-Korpik; Krzysztof Walczewski (PLoS ONE, 2026)
This study addresses a largely unexplored area in schizophrenia: the relationship between affective functioning and sensory perception assessed through objective, quantifiable methods. To the best of the authors’ knowledge, this is the first study to assess the electrical sensory threshold in individuals with schizophrenia using transcutaneous electrical nerve stimulation (TENS). It was hypothesized that patients with schizophrenia require higher current intensity to reach the sensory threshold and that an association exists between anhedonia and the subjective evaluation of the electrical stimulus. The study was based on an objective assessment of the sensory threshold using electrical stimulation. A gradually increasing electrical pulse was applied until the sensory threshold, defined as the minimum tingling sensation perceived by the participant, was reached. The study included 108 individuals diagnosed with schizophrenia and 59 participants in the control group. Various dimensions of anhedonia were assessed using the Dimensional Anhedonia Rating Scale (DARS). Quality of life and its domains were assessed using the WHOQOL-BREF. Participants reporting higher levels of sensory anhedonia rated the electrical stimulus as less pleasant. A negative correlation was observed between the pleasantness of the stimulus and both patient age and treatment duration. Furthermore, individuals whose clinical improvement was rated by the physician as more pronounced than at baseline exhibited greater sensitivity to the electrical stimulus. These findings suggest that anhedonia should be considered not only as a core symptom of schizophrenia, but also as a factor influencing patients’ adaptation in multiple domains, including sensory processing. Addressing anhedonia may therefore be a relevant target for both preventive strategies and rehabilitation programs.